Hind Tea Pvt. Ltd. : transitioning across generations - Kajal, Satbir Singh, (SAGE Knowledge. Cases., 2017)
The case discusses Hind Tea Pvt. Ltd. (HTPL), an SME in India that is 100% owned by the Wadhwa family. HTPL procures processed tea from auctions and sell it to distributors under its own brand names. The case describes the journey of two brothers and how the second generation of the family takes over and aspires to make the company a national level player. The third generation of the family is also being groomed for the business and aspires to take the company to an international level. These aspirations pose new demands on the owners and the business.